2022
DOI: 10.3390/cells11081362
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Link between Gut Dysbiosis and Major Depression: An Extensive Review

Abstract: Depression is a highly common mental disorder, which is often multifactorial with sex, genetic, environmental, and/or psychological causes. Recent advancements in biomedical research have demonstrated a clear correlation between gut dysbiosis (GD) or gut microbial dysbiosis and the development of anxiety or depressive behaviors. The gut microbiome communicates with the brain through the neural, immune, and metabolic pathways, either directly (via vagal nerves) or indirectly (via gut- and microbial-derived meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 194 publications
0
36
0
Order By: Relevance
“…Novel findings pertaining to this study suggest that the MGB axis plays a potential role in the regulation of depressive symptoms and sleep disturbance (Naseribafrouei et al, 2014; Smith et al, 2019). Specifically, the GM affects the central nervous system through various bidirectional biological pathways either directly through anatomical connections (e.g., vagal nerves) or indirectly via microbial-derived metabolites (e.g., SCFAs) and entero-and neuroendocrine peptides (Sonali et al, 2022). The bidirectional nature of the MGB axis has been widely implicated in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Novel findings pertaining to this study suggest that the MGB axis plays a potential role in the regulation of depressive symptoms and sleep disturbance (Naseribafrouei et al, 2014; Smith et al, 2019). Specifically, the GM affects the central nervous system through various bidirectional biological pathways either directly through anatomical connections (e.g., vagal nerves) or indirectly via microbial-derived metabolites (e.g., SCFAs) and entero-and neuroendocrine peptides (Sonali et al, 2022). The bidirectional nature of the MGB axis has been widely implicated in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…From a phase 3 randomized, controlled trial, using a the CDiff32, a CDI-specific measure of QoL, patients receiving an LBP reported significant improvements in mental health-related QoL as early as week 1, which continued throughout the 8-week blinded study period ( 75 ). While definitive mechanisms linking changes in the gut microbiota to mental state have not been determined, it is clear that there is a link ( 76 ).…”
Section: Approaches To Restoring the Gut Microbiotamentioning
confidence: 99%
“…Currently, there is growing evidence proposing that dysregulation in the composition of the gut microbiota is related to the pathophysiology of anxiety and depression disorders due to its interaction with neuroimmune, neuroendocrine, and neural pathways [ 66 , 67 ]. These pathways are part of the brain–gut–microbiota axis that may modulate brain development and function, which also impacts on behavior.…”
Section: Biochemical and Pharmacological Activity Of Flavonoid Chrysinmentioning
confidence: 99%